2020
DOI: 10.3389/fcell.2020.00524
|View full text |Cite
|
Sign up to set email alerts
|

Apoptin as a Tumor-Specific Therapeutic Agent: Current Perspective on Mechanism of Action and Delivery Systems

Abstract: Cancer remains one of the leading causes of death worldwide in humans and animals. Conventional treatment regimens often fail to produce the desired outcome due to disturbances in cell physiology that arise during the process of transformation. Additionally, development of treatment regimens with no or minimum side-effects is one of the thrust areas of modern cancer research. Oncolytic viral gene therapy employs certain viral genes which on ectopic expression find and selectively destroy malignant cells, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 173 publications
0
22
0
Order By: Relevance
“…Very interesting is the notion that two de novo proteins are known to exert functions that are not virus-specific. They are the apoptin of Chicken anemia virus, which induces cell death in a broad range of human tumour cell lines but not in normal cells [57,58], and the protein X of Borna disease virus, which shows protective properties against neurodegeneration in vitro and in vivo [59,60]. Symmetric evolution (similar selection pressures on the two proteins) was found in the remaining 37 overlaps of the dataset [51].…”
Section: Symmetric and Asymmetric Evolution In Viral Overlapping Genesmentioning
confidence: 99%
“…Very interesting is the notion that two de novo proteins are known to exert functions that are not virus-specific. They are the apoptin of Chicken anemia virus, which induces cell death in a broad range of human tumour cell lines but not in normal cells [57,58], and the protein X of Borna disease virus, which shows protective properties against neurodegeneration in vitro and in vivo [59,60]. Symmetric evolution (similar selection pressures on the two proteins) was found in the remaining 37 overlaps of the dataset [51].…”
Section: Symmetric and Asymmetric Evolution In Viral Overlapping Genesmentioning
confidence: 99%
“…Oncolytic Adenoviruses are novel and highly effective gene delivery vectors which can be modified to express specific genes in the target cancer cell, eventually causing cell lysis and death [1].Our laboratory developed an Ad-vp3 (Ad5-apoptin) that expresses apoptin. Another Ad-vt (Ad5-apoptin-hTERTp-E1a) that can continuously express apoptin in the cancer cell via an hTERT promoter-driven was also developed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study indicated that the infection induced by avian smallpox virus (without the ability of proliferation, functioning as a vector for the apoptin gene) resulted in significant apoptosis induction in hepatoma cells, suggesting the inhabitation of subcutaneously implanted tumor cells in mice. 30 While the apoptin protein can function with specificity in the apoptosis induction of the transformed (cancerous) cells, the healthy cells are not affected by this process. 1 The specificity of apoptin depends on where it is found inside the cell; therefore, its specificity to the cancer cell is increased compared to other healthy cells, due to the transmission of this molecule from the outside of the cell to the nucleus during the process of attachment to the cancer cells.…”
Section: Discussionmentioning
confidence: 99%